Uji Kualitas Air Sungai Raci Secara Perspektif Berdasarkan Parameter TDS (Total Dissolved Solid) - Ayu Larasati , Agnes Diah (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
Raci River is a river close to residential areas and also close to industrial areas. Most Raci communities use the Raci river as the main water body for domestic activities of racers, as well as being the final waste water body for industrial estates, so that the quality of Raci river water continues to decline from year to year. This study aims to analyze the water quality of the river in perspective using TDS parameters so that it can determine the level of pollution in the river Raci based on TDS parameters and also can determine the factors that affect the levels of TDS in the river Raci. The location of this research is in the area of ??Raci, Kab. Pasuruan, while for testing the river water is carried out at the UHD Laboratory of DLH District. Pasuruan. The method used in this study is the gravimetric method. The results of this study indicate that the levels of TDS in all three points, namely upstream, middle, downstream, showed a significant difference, the level of TDS to the advanced river flow is greater than in the initial water body. Raci river water quality based on TDS parameters exceeds the quality standard, which is more than 1000 mg / L based on the East Java Regional Regulation Year 2 of 2008 concerning Management of Water Quality and Water Pollution Control in East Java Province, so further research is needed to identify more about the pollution level category river water in the raci area.